2015
DOI: 10.5335/ciatec.v7i1.4328
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico Da Logística Reversa De Lâmpadas Por Meio Da Avaliação De Ciclo De Vida

Abstract: Este estudo objetiva realizar uma avaliação da logística reversa de lâmpadas fluorescentes inservíveis no município de Santa Cruz do Sul/RS, tendo em vista a avaliação ambiental de diferentes modelos de gerenciamento. Para tal, foi realizado um levantamento da situação existente na região de estudo, ao nível das quantidades e modelos de logística reversa viáveis. O estudo foi realizado considerando três cenários de gerenciamento das lâmpadas fluorescentes inservíveis. A análise ambiental dos referidos cenários… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Oliveira & Magrini (2017), evaluated different options for the EoL of lubricant oil plastic containers finding the potential of reduction on the environmental impacts when deposition in industrial landfills is avoided. Zappe et al (2015) focused on RL and EoL options for fluorescent lamps and found that lamp transportation had the largest contribution to the overall environmental impact amongst the evaluated chain stages. Also, Oliveira (2019) evaluated RL for EPPC in four central units located in two different states and found that the distance between these units and end-of-life destinations concentrated most potential environmental impacts.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…Oliveira & Magrini (2017), evaluated different options for the EoL of lubricant oil plastic containers finding the potential of reduction on the environmental impacts when deposition in industrial landfills is avoided. Zappe et al (2015) focused on RL and EoL options for fluorescent lamps and found that lamp transportation had the largest contribution to the overall environmental impact amongst the evaluated chain stages. Also, Oliveira (2019) evaluated RL for EPPC in four central units located in two different states and found that the distance between these units and end-of-life destinations concentrated most potential environmental impacts.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%